2012
DOI: 10.1152/physrev.00037.2010
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptins and Reproduction: Physiological Roles and Regulatory Mechanisms

Abstract: Procreation is essential for survival of species. Not surprisingly, complex neuronal networks have evolved to mediate the diverse internal and external environmental inputs that regulate reproduction in vertebrates. Ultimately, these regulatory factors impinge, directly or indirectly, on a final common pathway, the neurons producing the gonadotropin-releasing hormone (GnRH), which stimulates pituitary gonadotropin secretion and thereby gonadal function. Compelling evidence, accumulated in the last few years, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
565
1
31

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 687 publications
(611 citation statements)
references
References 513 publications
(1,184 reference statements)
14
565
1
31
Order By: Relevance
“…Extensive experimental studies in various species have demonstrated that kisspeptin-producing neurons are major afferents to GnRH neurons and are essential for different aspects of GnRH function, ranging from the tonic feedback control of GnRH and/or gonadotropin secretion to generation of the pre-ovulatory surge responsible for ovulation. 43 Interestingly, although kisspeptins do not seem to be mandatory for proper GnRH neuron migration, compelling experimental work has documented that populations of kisspeptin neurons undergo a dynamic process of prenatal and postnatal maturation that enables them to establish connections with GnRH neurons early in development 44 (under the control of steroid hormones [45][46][47] ). Similarly, identification of mutations in TAC3 (encoding tachykinin-3, which is cleaved to form neurokinin-B) and TACR3 (encoding tachykinin receptor 3; also known as neuromedin-K receptor [NKR]) [48][49][50] in patients with CHH highlights the important role of members of the tachykinin family in the control of GnRH neurons.…”
Section: Biology Of the Gnrh Neuronal Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive experimental studies in various species have demonstrated that kisspeptin-producing neurons are major afferents to GnRH neurons and are essential for different aspects of GnRH function, ranging from the tonic feedback control of GnRH and/or gonadotropin secretion to generation of the pre-ovulatory surge responsible for ovulation. 43 Interestingly, although kisspeptins do not seem to be mandatory for proper GnRH neuron migration, compelling experimental work has documented that populations of kisspeptin neurons undergo a dynamic process of prenatal and postnatal maturation that enables them to establish connections with GnRH neurons early in development 44 (under the control of steroid hormones [45][46][47] ). Similarly, identification of mutations in TAC3 (encoding tachykinin-3, which is cleaved to form neurokinin-B) and TACR3 (encoding tachykinin receptor 3; also known as neuromedin-K receptor [NKR]) [48][49][50] in patients with CHH highlights the important role of members of the tachykinin family in the control of GnRH neurons.…”
Section: Biology Of the Gnrh Neuronal Systemmentioning
confidence: 99%
“…58 Exactly how the effects of leptin are transmitted to GnRH neurons is unknown, as this neuro nal population does not express the leptin receptor. 59 Experimental data suggest that kisspeptin neurons are sensitive to changes in leptin concentrations and metabolic conditions, 43 yet they apparently do not express functional leptin receptor, which indicates the mode of action is indirect. 60 Primary leptin targets for conduction of its reproductive effects probably include nitric oxideproducing neurons in the pre-optic hypothalamus 61 and neuronal circuits in the ventral premammillary nucleus, 60 which might transmit metabolic information to GnRH neurons through kiss peptin dependent and/or independent pathways.…”
Section: Virilization (Male)mentioning
confidence: 99%
“…In fact, identification of Kp is now considered as one of the major breakthroughs in reproductive biology since the isolation of GnRH back in the early 1970s (7,11). As extensively revewed elsewhere, kisspeptins, which include Kp-54 and Kp-10, are a family of structurally related peptides, encoded by the Kiss1 gene, that act via the G protein-coupled receptor Gpr54 (also termed Kiss1R) (7,8,10). The first evidence about the reproductive roles of kisspeptins and Gpr54 dates back to late 2003, when inactivating mutations of the receptor were described in patients with hypogonadotropic hypogonadism (HH), a pathological condition of impuberism and infertility of central origin (13,14).…”
Section: Kisspeptins: Major Gatekeepers Of Pubertymentioning
confidence: 99%
“…Without any doubt, a major development in the field came with the identification of kisspeptins (Kp) as essential gatekeepers of puberty, a role that has drawn considerable attention in recent years (7,8,9,10), and will be discussed herein, especially in light of recent developments that seem to challenge the dogma of an indispensable role of kisspeptins in puberty. In addition, attention will be paid in this review to summarize some illustrative examples of the identification of additional central transmitters and regulatory mechanisms (putatively) involved in the control of puberty and its modulation by the metabolic status.…”
mentioning
confidence: 99%
“…Metabolic effects on reproduction in humans which may involve KP dysregulation, include hypothalamic amenorrhea, (anorexia nervosa being an extreme example), and PCOS, which is characterized by increased LH pulse frequency and is often associated with obesity 68 . For detailed reference to the diverse physiological and pathophysiological regulation of KP the reader is referred to comprehensive reviews 76,105,106 .…”
Section: Experimental Diabetes Mellitus Induced Bymentioning
confidence: 99%